Analysis of a successive approximation analog-to-digital converter - Chong, Chee Hock. (2008)
This report describes the detail analysis of an 8-bit successive approximation analog-to-digital converter (LC520). To enhance the understanding of data conversion using the successive approximation method, a very comprehensive write-up on the theory of data acquisition and conversion were performed. The function and operating principles of the various components used in this 8-bit successive approximation analog-to-digital converter were explained in detail. The detail explanation of the bit-by-bit conversion of analog data to digital data, with detail clock transition was performed.